Incomplete Justice: The Costs of Partial Indemnity - Abdulla, Adil (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2022)
In the mid-twentieth century, Ontario abandoned a simple, full indemnity costs rule in favour of a discretionary, partial indemnity costs regime with hundreds of sub-rules. This article argues that this was a mistake. Partial indemnity has no doctrinal, principled, or practical benefits that cannot be incorporated into a full costs regime. Additionally, partial indemnity carries significant costs to access to justice. Instead, this article proposes a costs regime that incorporates the best features of both the old rule and the new regime. In brief, it proposes a full indemnity rule; capped at the losing party’s costs; with exceptions for divided success, impecuniosity, and public interest cases; and discretionary fines for engaging in misconduct or dilatory tactics. Collectively, these rules would advance access to justice more than the existing costs regime.